To Study Bone Tissue Mineral Density and its Disorders in Patients with Celiac Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article analyzes decreased bone tissue mineral density and its disorders in patients with celiac disease. Celiac disease causes autoimmune inflammation of the intestinal mucosa, causing impaired absorption of calcium and vitamin D. This increases the risk of developing osteopenia and osteoporosis. The study discusses methods for assessing bone density, the effects of the disease on bone metabolism, and preventive measures. It also discusses the importance of dietetics and the positive effects of a gluten-free diet on bone health.